2001
DOI: 10.1046/j.1468-1331.2001.00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin type A injections in the spastic upper extremity of children with hemiplegia: child characteristics that predict a positive outcome

Abstract: Evidence is increasing to suggest that botulinum toxin type A (BTX-A) plays a role in the management of upper extremity spasticity in the paediatric population. However, little information is available on the clinical characteristics of the child that predict a response to this intervention. Our research group previously published a randomized controlled trial demonstrating that BTX-A injection improves function of the upper extremity of children with spastic hemiplegia. In the present paper, we evaluate the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 13 publications
(13 reference statements)
0
55
0
3
Order By: Relevance
“…For instance, when injecting muscles of the forearm and hand, grip strength may be affected. A study by Fehlings et al 5 outlines the importance of adequate baseline grip strength in predicting a positive response to the upper extremity BTX-A injections. The dependence on adequate grip strength poses a potential problem with the use of a high dose of BTX-A.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, when injecting muscles of the forearm and hand, grip strength may be affected. A study by Fehlings et al 5 outlines the importance of adequate baseline grip strength in predicting a positive response to the upper extremity BTX-A injections. The dependence on adequate grip strength poses a potential problem with the use of a high dose of BTX-A.…”
mentioning
confidence: 99%
“…The high dose was in the range of BTX-A that is in current clinical usage and in published articles. 3,5,[7][8][9] The low-dose group received 50% of the dosage of the high-dose group for each muscle group injected. We hypothesized that a low dose would be more effective because it would permit a reduction in tone and subsequent improvement in function without causing significant weakness.…”
mentioning
confidence: 99%
“…This is not surprising since over 60% of both cohorts were tetraplegic and up to another 34% were either diplegic or hemiplegic. Moreover, it has been reported that if the hand is weak initially, botulinum toxin can decrease hand function [12].…”
Section: Discussionmentioning
confidence: 99%
“…Использование многоуровневых инъекций средни-ми дозами БТА (12-15 Ед/кг) показало свою эффектив-ность в коррекции эквинусной деформации стоп [26], улучшении функции голеностопного сустава [27,28], силы захвата кисти [29] и общей двигательной активности пациентов с ДЦП. Более того, в ряде работ было показа-но, что средние дозы были более эффективными по срав-нению с низкими дозами, использованными в первых исследованиях [23,30].…”
Section: Introductionunclassified